2022
DOI: 10.1111/nep.14039
|View full text |Cite
|
Sign up to set email alerts
|

Profile of urinary exosomal microRNAs and their contribution to diabetic kidney disease through a predictive classification model

Abstract: Aim Evaluate the expression of exomiRs‐126, ‐146, and ‐155 in urinary exosomes of patients with T2DM and diabetic kidney disease to establish a predictive classification model with exomiRs and clinical variables in order to determine their contribution to DKD. Methods The study group included 92 subjects: 64 patients diagnosed with T2DM subclassified into two groups with albuminuria (T2DM with albuminuria, n = 30) and without albuminuria (TD2M, n = 34) as well as 28 healthy, non‐diabetic participants. Exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Only limited medical fields have investigated urinary microRNA profiles. Examples are metabolic diseases, chronic kidney disease, and cancers such as clear cell renal cell carcinoma, and prostate cancer [8,13–16]. The main innovation of this study was to explore urinary microRNAs as a novel resource to be potentially utilized for monitoring the pregnancy course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only limited medical fields have investigated urinary microRNA profiles. Examples are metabolic diseases, chronic kidney disease, and cancers such as clear cell renal cell carcinoma, and prostate cancer [8,13–16]. The main innovation of this study was to explore urinary microRNAs as a novel resource to be potentially utilized for monitoring the pregnancy course.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited medical fields have investigated urinary microRNA profiles. Examples are metabolic diseases, chronic kidney disease, and cancers such as clear cell renal cell carcinoma, and prostate cancer [8,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The group was able to create various models that predicted the extent of renal fibrosis with high AUCs (i.e., 0.9 and above) (Lv et al, 2013). More recent work focused on DN, was able to create a multivariable model using urine exosomal miR-126, miR-146, miR-155, as well as other paraclinical data, to predict between patients with T2DM with and without DN while maintaining high sensitivity (0.963) and specificity (0.935) (González-Palomo et al, 2022). These findings, as well as those of other studies that identified exosomal miRNA biomarkers for DN are summarized in Table 3 and Figure 2 (Eissa et al, 2016a;Eissa et al, 2016b;Delić et al, 2016;Mohan et al, 2016;Xie et al, 2017;Li et al, 2018;Zang et al, 2019).…”
Section: Diabetic Nephropathymentioning
confidence: 99%

Exosomal RNA in renal diseases

González Palomo,
Turiján Espinoza,
Jiménez Avalos
et al. 2024
Exosomal RNA